2001
DOI: 10.1007/s004280000286
|View full text |Cite
|
Sign up to set email alerts
|

Protein expression of matrix metalloproteinases 2 and 9 and tissue inhibitors of metalloproteinase 1 and 2 in papillary thyroid carcinomas

Abstract: Matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs) play an important role in tumor invasion and metastasis. There have been only a few studies on the protein expression of MMPs and TIMPs in thyroid carcinomas. Therefore, we investigated the protein expression of MMP-2, MMP-9, TIMP-1 and TIMP-2 in 86 papillary thyroid carcinomas using immunohistochemistry, semiquantitative scoring morphometry of immunohistochemistry, gelatin zymography, and western blotting. We also examined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
2
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 31 publications
5
85
2
2
Order By: Relevance
“…Expression of MMP-2 and MMP-9 is elevated in carcinomas in association with low differentiation grade and accelerated tumour progression in oral carcinoma, 30 lung adenocarcinoma, 31 bladder 32 and ovarian carcinoma 33 and papillary thyroid carcinoma. 34 MMP-2 expression correlates also with advanced disease in neuroblastoma. 35 MMP-2 36,37 or MT1-MMP are not expressed in cervical neoplasia but their expression levels are high in cervical carcinoma and correlate with advanced stage.…”
Section: Mmps In Malignant Transformation and Cancer Progressionmentioning
confidence: 97%
See 1 more Smart Citation
“…Expression of MMP-2 and MMP-9 is elevated in carcinomas in association with low differentiation grade and accelerated tumour progression in oral carcinoma, 30 lung adenocarcinoma, 31 bladder 32 and ovarian carcinoma 33 and papillary thyroid carcinoma. 34 MMP-2 expression correlates also with advanced disease in neuroblastoma. 35 MMP-2 36,37 or MT1-MMP are not expressed in cervical neoplasia but their expression levels are high in cervical carcinoma and correlate with advanced stage.…”
Section: Mmps In Malignant Transformation and Cancer Progressionmentioning
confidence: 97%
“…47 Invasive behavior of gastric carcinoma is associated with MT1-MMP expression 48 and bladder carcinoma with both MMP-2 and MT1-MMP expression. 49 In papillary thyroid carcinoma, high MMP-2 and MMP-9 expression 34 Recent observations show that insertion of G nucleotide at Ϫ1607 bp in MMP-1 promoter generates a new ETS binding site and increases the transcription of the MMP-1 gene. 50 Homozygosity for this single nucleotide insertion polymorphism (2G allele) has been shown to correlate with invasiveness of colorectal cancer 51 and cutaneous melanoma.…”
Section: Mmps In Tumor Invasionmentioning
confidence: 99%
“…A large body of experimental evidence suggested that MMPs essentially contributed to the maintenance of tumor growth in primary and metastatic sites [55][56][57]. Adhami et al [58] have shown that p.o.…”
Section: Inhibition Of the Cancer Progression Stage By Egcgmentioning
confidence: 99%
“…Although some correlation studies support an association between specific genetic alterations and aggressive cancer behavior (6)(7)(8)(9), there are a number of events that are found nearly exclusively in aggressive PTCs, including mutations of P53 (10,11), dysregulated ␤-catenin signaling (12), up-regulation of cyclin D1 (13), and overexpression of metastasis-promoting, angiogenic, and/or cell adhesion-related genes (14)(15)(16)(17)(18)(19)(20). We have determined that invasive regions of primary PTCs are frequently characterized by enhanced Akt activity and cytosolic p27 localization (21,22).…”
mentioning
confidence: 99%